Beispiel Nr: 11
$ \text{Gegeben:} \\ a1 \cdot x + b1\cdot y + c1\cdot z=d1\\ a2\cdot x + b2\cdot y + c2\cdot z=d2\\ a3\cdot x + b3\cdot y + c3\cdot z=d3\\ \\ \text{Gesucht:} \\\text{x,y,z} \\ \\ \textbf{Gegeben:} \\ 11 x +13 + 4 z=37\\ 12 x +14 y + 5 z=40\\ 9 x +3 y + 3 z=15\\ \\ \\ \textbf{Rechnung:} \\\small \begin{array}{l} 11x+13y+4z=37 \\ 12x+14y+5z=40 \\ 9x+3y+3z=15 \\ \\ \end{array} \qquad \small \begin{array}{ccc|cc } x & y & z & & \\ \hline11 & 13 & 4 & 37 \\ 12 & 14 & 5 & 40 \\ 9 & 3 & 3 & 15 \\ \end{array} \\ \\ \begin{array}{l}\text{Zeile}2=\text{Zeile}2\cdot 11\text{-Zeile}1\cdot 12 \\z2s1=12\cdot 11-11\cdot 12 =0 \\ z2s2=14\cdot 11-13\cdot 12 =-2 \\ z2s3=5\cdot 11-4\cdot 12 =7 \\ z2s4=40\cdot 11-37\cdot 12 =-4 \\ \end{array}\qquad \small \begin{array}{ccc|cc } x & y & z & & \\ \hline11 & 13 & 4 & 37 \\ 0 & -2 & 7 & -4 \\ 9 & 3 & 3 & 15 \\ \end{array} \\ \\ \begin{array}{l}\text{Zeile}3=\text{Zeile}3\cdot 11\text{-Zeile}1\cdot 9 \\z3s1=9\cdot 11-11\cdot 9 =0 \\ z3s2=3\cdot 11-13\cdot 9 =-84 \\ z3s3=3\cdot 11-4\cdot 9 =-3 \\ z3s4=15\cdot 11-37\cdot 9 =-168 \\ \end{array}\qquad \small \begin{array}{ccc|cc } x & y & z & & \\ \hline11 & 13 & 4 & 37 \\ 0 & -2 & 7 & -4 \\ 0 & -84 & -3 & -168 \\ \end{array} \\ \\ \begin{array}{l}\text{Zeile}3=\text{Zeile}3\cdot (-2)\text{-Zeile}2\cdot (-84) \\z3s2=(-84)\cdot -2-(-2)\cdot (-84) =0 \\ z3s3=(-3)\cdot -2-7\cdot (-84) =594 \\ z3s4=(-168)\cdot -2-(-4)\cdot (-84) =0 \\ \end{array}\qquad \small \begin{array}{ccc|cc } x & y & z & & \\ \hline11 & 13 & 4 & 37 \\ 0 & -2 & 7 & -4 \\ 0 & 0 & 594 & 0 \\ \end{array} \\ \\ z=\frac{0}{594}=0\\y \cdot (-2)+7\cdot0=(-4)\\y= 2\\x\cdot 11+13\cdot2+4\cdot0=37\\x= 1\\L=\{1/2/0\}$